INNOVATIVE METHODS OF TEACHING HISTOLOGY TO MEDICAL UNIVERSITY STUDENTS (Scientific journal of the Fergana State University, 2025)
This article examines the limitations of traditional histology teaching methods in medical universities and highlights the advantages of innovative approaches. It presents modern pedagogical technologies, such as virtual microscopy, 3D modeling, online educational platforms, and gamification techniques, which significantly enhance students’ theoretical knowledge, practical skills, and analytical thinking. A mixed-method approach was used to assess students’ knowledge levels and the development of their practical competencies. The study’s findings demonstrate that innovative methods not only expand the content of histology courses but also effectively support the preparation of students for clinical practice. Future directions include the further expansion of a hybrid education model, the strengthening of technical infrastructure, and the continuous professional development of educators in utilizing modern ICT tools